Gambaran Moral reasoning remaja dengan Pengasuhan Reflektif Ibu Pekerja Seks Komersial - Zainuddin, Kurniati; Muhammad Daud; St Nur Azisah (Universitas Islam Negeri Alauddin Makassar, 2025)
This research explores the dynamics of moral reasoning development in adolescents raised by single mothers working as Commercial Sex Workers (CSW) who practice reflective parenting. Through a single case study of a resident at Mattiro Deceng Social Institution, this research examines how reflective parenting implemented by CSW mothers contributes to the formation of children's moral reasoning that enables them to resist negative influences from the localization environment. The research employs a qualitative approach with in-depth interviews and participant observation. Thematic analysis identified three main themes in reflective parenting: (1) narrative transparency and expressions of regret, (2) consequential dialogue about social stigma, and (3) facilitation of moral autonomy and future aspirations. Findings suggest that reflective parenting contributes to the formation of adolescent moral reasoning through a value internalization process involving critical awareness of the moral consequences of life choices. This research provides a new perspective in understanding protective factors of parenting in risky social contexts and their implications for family-centered psychosocial interventions in marginalized communities.